Pentingnya Gaya Hidup Sehat terhadap Konsentrasi Belajar Siswa: Studi Cross Sectional: The Importance of a Healthy Lifestyle for Students’ Learning Concentration: Cross-Sectional Study - Anwary, Muhammad Azhar; Nurhamidi, Nurhamidi; Hariati, Niken Widyastuti (Jurnal Ilmu Gizi dan Dietetik, 2026)
Learning concentration is an essential component in supporting students' academic achievement. Both internal and external factors can affect concentration levels, including sleep quality, iron intake, and breakfast habits. This study aims to examine the relationship between sleep quality, frequency of iron consumption, and breakfast habits with students' learning concentration at MA Al Irsyad Sungai Tuan. This study applied an analytical observational design with a cross-sectional approach. A total of 48 students from grades X and XI who met the inclusion criteria were selected as respondents using a total sampling technique. Data were collected using standardized instruments, namely the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, the Food Frequency Questionnaire (FFQ) to measure the frequency of iron intake, and an additional questionnaire to assess breakfast habits and learning concentration levels. Data analysis was conducted using Spearman's Rank correlation test to identify relationships between variables. The results showed significant correlations between sleep quality (p=0.000), frequency of iron consumption (p=0.001), and breakfast habits (p=0.002) with students’ learning concentration. These findings indicate that students with good sleep quality, adequate iron intake, and regular breakfast habits tend to have higher levels of learning concentration. In conclusion, sleep quality, frequency of iron consumption, and breakfast habits are important determinants in supporting students’ learning concentration. Therefore, the results of this study are expected to serve as a basis for schools and parents to pay more attention to students' lifestyle factors in order to promote optimal academic performance.